The Quality Analysis of Vermicelli From Corn (Zea mays L) and Potato (Solanum tuberosum L) Starch - Probowati, Banun Diyah; Burhan, Burhan; Indarto, Cahyo; Farikh, Muhammad Dawil (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2024)
Vermicelli was a food made from flour with a particular characteristic in the form of transparent thread and could be produced from corn and potato starch. It must appropriate the quality standards. The Objectives of the research are: (1) to determine the effect of formulation and drying time on the water content of vermicelli, (2) to determine the appropriate formulation of corn and potato starch, (3) to evaluate the quality of durability, (4) to determine the quality of the total protein content in vermicelli made from corn and potato starch. The experimental design of making vermicelli used the complete random design (CRD) method with 2 factors (composition of corn and potato starch) and drying time (120 and 180 minutes). The quality parameters of vermicelli are water content, sensory analysis, durability, and protein content. The results showed that the drying time has a significant effect on the water content of vermicelli. Still, the interaction of formulation and drying time factors did not significantly influence the water content of vermicelli. The overall preference for sensory analysis showed that the vermicelli formulation of 60:40 for corn and potato starch in 180 minutes of drying was the best formulation for Vermicelli-based corn and potato starch. The durability of this vermicelli was appropriate to quality standards (not easily crushed). The protein content was 1.53%, which is not appropriate to the quality standard of SNI 01-2975-2006 (minimum 4%). The novelty of the research was the best composition of materials to produce vermicelli from corn and potato starch and the drying time to produce it. Suggestions for further research could be to produce vermicelli with the composition of materials by adding nuts, eggs, or other ingredients to increase protein content and to analyze its quality.